LAW OF WARRANTY OF HALAL PRODUCTS AS A PROTECTION OF MUSLIM CONSUMERS IN INDONESIA - Nurul Hakim (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
The law that provides legal protection for Muslim consumers in Indonesia has long been missed. This is because the number of products sold and circulated in Indonesia is questionable as halal, while Muslims are the largest community in Indonesia. Based on these facts, it is a necessity that Muslims need protection for what they consume and the State is obliged to provide that protection. The basis for the need for regulations related to halal products is the existence of an order from the Koran for Muslims to consume halal and good food. The Draft Law on Halal Products itself is in the process of discussing fiercely, because there are several parties who state that there is no need for the state to interfere too much with the halal or haram that is consumed by the public. Finally, Law Number 33 of 2014 concerning Guarantee of Halal Products was issued, even though it was at the end of Susilo Bambang Yudhoyono's reign. The issuance of Law Number 33 of 2014, at most gives an order to producers to immediately process their halal guarantees to the Indonesian Ulema Council to issue halal certificates.